LEVEL OF D-DIMER AND C- REACTIVE PROTEIN AMONG COVID-19 PATIENTS IN RELATION TO DIFFERENT AGES AND GENDERS - ABDULLAH, SAKAR AHMAD; SMAIL, HAREM OTHMAN; RAHIM, ALAA AHMED; MUHAMAD, TANYA KAMIL; MAJID, BANWAN; ROSTAM, BINAY; NAWROZ, NAZ; AWAT, SIVER; KAMAL, DYARI (Journal of Duhok University, 2023)
coronavirus disease of 2019 (COVID-19) is a new infectious disease spreading worldwide rapidly. COVID-19 has been associated with a risk of thrombosis, which an increase in the level of D-dimer can detect. D-dimer is a small fragment of protein present in the blood after blood clot degradation. This research aimed to evaluate the level of D-Dimer and C- reactive protein in COVID-19 patients and ascertain the relation of these markers with age and gender. From December 2020 to January 2021, patients with laboratory reports of Covid-19 were retrospectively enrolled in different hospitals and private laboratories. We collected 253 cases of the D-dimer test for different ages and genders and 204 cases of C- reactive protein test with D-dimer to detect the severity of the disease. An increased level of D-dimer of more than 0.5 mcg/ml was reported in 105 patients (41.5%). According to gender, 43.7% of males and 38.79% of females have elevated D-dimer levels. In patients with COVID-19, D-dimer levels greater than 0.5mcg/mL could accurately predict in-hospital morbidity and mortality. Therefore, D-dimer has been proposed as a possible early and effective marker for improved management of COVID-19 patients